The influence of entrepreneurial thinking on the sustainability of small and medium enterprises in Sukabumi: the moderating role of social media - Gunawan, Ce; Febriyanti, Intan Rike (Jurnal Mantik, 2025)
Small and Medium Enterprises (SMEs) play a crucial role in supporting and boosting economic growth in Indonesia.  In recent years, SMEs have been acknowledged as key drivers of job creation in both developing and developed nations.  This research plays a vital role in understanding entrepreneurial thinking to support the growth of SMEs. The purpose of this study is to examine the influence of entrepreneurial thinking on the small and medium enterprises sustainability and to analyze the moderating role of social media. This research employs quantitative methods. The measurement and structural models were evaluated using Partial Least Squares Structural Equation Modeling (PLS-SEM) with the SmartPLS v.4.0 application to test the hypotheses based on data from a total of 379 respondents. The study found that entrepreneurial intuition, entrepreneurial alertness, and entrepreneurial turn have significantly effect on business sustainability. Social media moderate the effects of entrepreneurial intuition, entrepreneurial alertness, and entrepreneurial turn significantly effect on business sustainability. Entrepreneurial thinking enables the generation of new ideas and the implementation of innovative actions within small and medium businesses (SMEs). This mindset helps maintain and enhance the competitive position of businesses, creating a sustainable advantage in a challenging environment. Given the economic difficulties faced by Indonesia, the sustainability of SMEs is crucial to overcoming these challenges. Achieving this sustainability requires SMEs to first adopt and internalize entrepreneurial thinking processes